PENGARUH STRESOR RENJATAN LISTRIK PADA KADAR KOLESTEROL TOTAL PADA SERUM TIKUS JANTAN (Rattus norvegicus) STRAIN WISTAR - Agustin Wulan Suci Dharmayanti (Fakultas Kedokteran Gigi Universitas Jember, 2012)
Stres caused homeostasis disturbance. Stres induced glucocorticoid and catecholamine releasing. These hormone influenced lipid metabolism. The aim of this study is to know effect electrical foot shock to total cholesterol level in serum of male rats (Rattus norvegicus) strain Wistar. This study was experimental laboratory with the post test only kontrol group design. This study used 14 male rats that divided into 2 groups, kontrol and treatment. The treatment group, samples got stres from electrical foot shock for 14 days. On the 15th day, blood of samples was taken from intracardial. Then, blood samples were tested cholesterol total level by CHOD-PAP in photometric system. The result was analyzed by t-test. The result showed there was significant different between kontrol and treatment group. The conclusion describe that cholesterol total level in treatment group is higher than kontrol group.